Once smitten, twice shy eaudiobook - Liese, Chloe (Wilmot Sisters, 2025)
AN INSTANT USA TODAY BESTSELLER! Star-crossed lovers learn that practicing romance leads to the perfect happy ending in this steamy reimagining of Shakespeare’s Twelfth Night . Since heartbreak entered the scene, Juliet Wilmot, once a hopeless romantic, has sworn off love. But when she’s presented with the chance to revisit romance—purely for practice—with the gorgeous, off-limits guy she keeps serendipitously running into, it feels like a sign from the universe. Quiet, shy Will Orsino knows happily-ever-after isn’t on his horizon. Problem is, for the sake of the family business, marriage is. Resigned to the inevitable, but with no confidence he can woo a wife, he can hardly say no when fate hands him the alluring, unattainable woman he keeps crossing paths with, offering to help him learn the ropes of romance. Neither of them looking for love, Jules and Will agree they’re the perfect pair to practice romance. Except that practicing to perfection leads to an irresistible attraction. Their once smitten hearts, though still twice shy, might have happily-ever-after written in the stars for them, after all.